Ginkgolide as a Promising Multi-Target Therapeutic for Alzheimer's Disease: Targeting ApoE4 and Beyond - Beigh, Saba; Alsahag, Mansoor; Alisaac, Ali; Dar, Sajad Ahmad; Alyami, Mohammad H.; Ajlan, Soma E.; Malak, Hesham A.; Alshehri, Abdullateef Abdullah (Current Pharmaceutical Design, 2026)
IntroductionThe progressive neurodegenerative disease known as Alzheimer's disease (AD) is typified by neuroinflammation, amyloid-beta buildup, and cognitive impairment. Current pharmacological treatments merely alleviate symptoms, despite extensive research, which underscores the need for innovative, multi-target medicines. Since apolipoprotein E4 (ApoE4) is a significant genetic risk factor linked to the development of AD, it is a potentially effective treatment target. With their neuroprotective qualities, natural substances like Ginkgolide may help treat some diseases. This study investigates Ginkgolide's potential as a multi-target treatment for AD, with a particular emphasis on how it interacts with the ApoE4 N-terminal domain.MethodsThe interaction between Ginkgolide and ApoE4 (PDB ID: 8AX8) was assessed using pharmacokinetic profiling, molecular docking, and molecular dynamics (MD) simulations. MD simulations were used to determine stability, and AutoDock Vina was used to obtain the binding affinity. To predict pharmacokinetics and toxicity, SwissADME and PkCSM were employed. The effectiveness of ginkgolide was contextualized using comparative docking with curcumin and resveratrol.ResultsGinkgolide formed sustained hydrophobic contacts with important sites and demonstrated a substantial binding affinity (-7.1 kcal/mol) to ApoE4. MD simulations verified negligible fluctuations and complex stability over 100 ns. Pharmacokinetics showed no significant toxicity risks, good gastrointestinal absorption, and favorable blood-brain barrier permeability. In terms of binding affinity and stability, ginkgolide fared better than curcumin and resveratrol, indicating its greater therapeutic potential.DiscussionThe results indicate that ginkgolide effectively binds and stabilizes the ApoE4 N-terminal domain, supporting its potential role in modulating a key pathological factor in Alzheimer’s disease. Its superior pharmacokinetic profile and interaction dynamics compared to curcumin and resveratrol suggest a broader therapeutic relevance. These in silico insights provide a mechanistic basis for further investigation into ginkgolide’s neuroprotective effects.ConclusionThe results demonstrated ginkgolide as a potentially effective multi-target treatment for AD through ApoE4 regulation. It is a better option than other natural chemicals because of its potent binding affinity, stability, and pharmacokinetics. These findings highlight the value of in silico methods in the early stages of drug discovery and the need for additional experimental support before they can be used in clinical settings.
Keywords: multi-target therapy